The Effectiveness of Online Teaching Towards Students’ Interest in Learning Physics of The Grade- 9 Student in Yunnan Province - Yang, Songbiao; Songsiengchai, Saifon (Education, Science, and Technology International Conference, 2024)
This study took the 9th grade students of Kunming Changshui Experimental Middle School as the research subjects. The purpose of this study is: 1) To study online learning affects Students’ interest in learning Physics. 2) To compare the differences between online learning and traditional teaching in students' interest in learning physics. 3) To investigate how the teachers’ perspectives on online learning affect Students’ interest in learning Physics. This study adopted quantitative and qualitative research methods. To interpret the data, we used mean, standard deviation and narrative analysis for statistical analysis. The main research tools were questionnaires, tests and course plans, and teacher logs. The results showed that: 1) online learning affects students’ interest in learning Physics the overall mean score of all variables was 2.48, and the standard deviation was 0.64, indicating that the consistency of the respondents was generally high; 2) According to the test results, online learning was 69.36 and traditional learning was 75.84, 3) Teachers perspective presented that students who received online teaching performed better in some aspects and average in most aspects. These results show that online teaching did not improve students’ interest in learning, which harmed their learning outcomes. This study emphasizes the importance of students’ interest in learning. Suggestions include optimizing technical support for online teaching, improving course design, and enhancing interaction. Future research should explore technical support for online teaching, technical training for teachers, and longitudinal impact and integration to continuously improve online teaching strategies.